Relationship Between Food Insufficiency and HIV Infection Among Caregivers of Orphans and Vulnerable Children in Tanzania - Exavery A (Dove Medical Press, 2020)
Amon Exavery,1 John Charles,1 Erica Kuhlik,2 Asheri Barankena,1 Godfrey Martin Mubyazi,3 Levina Kikoyo,1 Elizabeth Jere1 1Pact, Dar es Salaam, Tanzania; 2Pact, Inc., Washington, DC 20036, USA; 3National Institute for Medical Research (NIMR), Dar es Salaam, TanzaniaCorrespondence: Amon Exavery Email aexavery@pactworld.orgBackground: Although Tanzania experiences a general decline in HIV prevalence, some populations such as caregivers of orphans may be at a higher risk than the general population, suggesting that infection pathways still need further exploration. This study examines how food insufficiency relates to HIV infection among caregivers of orphans and vulnerable children (OVC) in Tanzania.Data and Methods: Data are from a community-based, USAID-funded Kizazi Kipya project that aims at increasing the uptake of HIV services, as well as other health and social services by OVC and their caregivers in Tanzania. Caregivers who were enrolled in the project from January to July 2017 in seven regions of Tanzania, and had reported their HIV status to the project, were included in the analysis. While HIV status was the outcome, the main independent variable was food insufficiency which was assessed using the Household Hunger Scale (HHS). Using Stata (version 14.0; StataCorp LP, College Station, TX, USA), data analysis involved multilevel mixed-effects logistic regression..Results: Of the 47,617 caregivers analyzed (73.7% females), 61.8% and 4.6% were experiencing moderate and severe hunger, respectively. The overall HIV prevalence among the caregivers was 28.3%. Nevertheless, the prevalence was as high as 34.2% among caregivers in severe hunger households. Multivariate analysis revealed an increasing likelihood of being HIV positive as hunger increased (moderate hunger: OR=1.10, 95%CI: 1.03– 1.18; severe hunger: OR=1.51, 95%CI: 1.32– 1.74). These observations were adjusted for marital status, age, sex, education, place of residence, family size, disability status, and health insurance.Conclusion: Food insufficiency is associated with a higher likelihood of HIV infection among OVC caregivers in Tanzania, suggesting that improving access to adequate food has a potential to reduce HIV risks among them. Furthermore, food insufficiency could be considered an important criterion for targeting HIV testing and treatment services to expand coverage.Keywords: food insufficiency, food security, HIV, caregivers of orphans and vulnerable children, USAID Kizazi Kipya, Tanzania